Revitalisasi Manajemen Sumber Daya Manusia dalam Meningkatkan Mutu Madrasah Tsanawiyah Al Ma’arif Jemaja Kabupaten Kepulauan Anambas Kepulauan Riau - Madaniyah Madaniyah; Afriza Afriza; Agustiar Agustiar; Asrulla Asrulla (Journal of Innovative and Creativity, 2025)
This research aims to examine the revitalization of Human Resource Management (HRM) in improving the quality of education at Madrasah Tsanawiyah Al-Ma’arif Jemaja, Anambas Islands Regency, Riau Islands Province. Madrasah Tsanawiyah Al-Ma’arif faces various challenges, including a significant decline in student enrollment and suboptimal teaching quality. The research method used is a descriptive qualitative approach, with data collection techniques through interviews, observations, and documentation. The results show that HRM revitalization can improve the quality of education, although several obstacles still need to be addressed. This study provides recommendations for Madrasah Tsanawiyah Al-Ma’arif to enhance educational quality by strengthening human resource capacity, improving institutional management, and diversifying funding sources. The main factors contributing to the challenges include suboptimal human resource management, a shortage of qualified teachers, and limited funding and facilities. This research identifies the steps necessary for HRM revitalization, such as recruiting more qualified teachers, improving teacher competencies through continuous training programs, and strengthening more effective foundation management. Additionally, the study also examines the challenges faced in implementing revitalization efforts, stemming from internal aspects such as resource limitations and lack of community participation, as well as external aspects such as difficulties in securing funding.